Behaviour of cold-formed steel built-up battened columns composed of four lipped angles: Tests and numerical validation. Issue 1 (January 2020) - Anbarasu, M
This article mainly investigates the behaviour and strength of built-up battened box column composed of lipped angles under axial compression. Ten specimens were fabricated and tested under pinned with warping-restrained end condition including two different cross-section dimensions of columns with five different geometric lengths. Three material tensile coupon tests were conducted to obtain the material properties of the steel used for fabricating the test specimens. The overall initial geometric imperfections were measured. The plate slenderness, member slenderness, chord slenderness and slenderness of batten plates may affect the compression behaviour of cold-formed steel built-up battened box columns and were accordingly investigated. It was found that the chord slenderness significantly affects the compressive strength of the built-up columns. Test results, including the compression resistances, the load versus displacement responses and the deformed shapes were presented. The test strengths were compared with the design strengths predicted using the North American Specifications (AISI-S100:2016), EuroCode (EN1993-1-3:2006) and design equations proposed by EI Aghoury et al. The design strengths predictions by these two design standards were unconservative, with EI Aghoury et al.'s standard performing better. Finite-element models were developed and verified against the test results.